Establishing the Foundation to Support Health System Quality Improvement: Using a Hand Hygiene Initiative to Define the Process. Issue 1 (January 2021) - Anderson, Rebecca; Rosenberg, Alexandra; Garg, Swati; Nahass, Jennifer; Nenos, Andrew; Egorova, Natalia; Rowland, John; Mari, Joseph; LoPachin, Vicki
Abstract : Objectives: As hospitals are increasingly consolidating into larger health systems, they are becoming better positioned to have far reaching and material impacts on safety and quality of care. When the Mount Sinai Health System (MSHS) was formed in 2013, it sought to ensure the delivery of safe, high-quality care to every patient. In 2014, the MSHS addressed hand hygiene as the first major system-wide process improvement project focused on quality and safety. The goals of this study were to evaluate a system-wide hand hygiene program and to create a foundation for future process improvement projects. Methods: The MSHS implemented the Joint Commission's Targeted Solutions Tool as a way to improve hand hygiene compliance and reduce harm from hospital-acquired infections, specifically Clostridium difficile infections. A multifaceted approach was used to improve hand hygiene and promote a culture of patient safety. Results: The MSHS improved hand hygiene compliance by approximately 20% from a baseline compliance of 63.3% to an intervention compliance of 82.8% ( P < 0.001). Additional correlation analysis revealed a significant correlation between increasing hand hygiene compliance and reduction in C. difficile infections. Conclusions: Through a focus on leadership engagement, data transparency, data and observer management, and system-wide communication of best practices, the MSHS was able to improve hand hygiene compliance, reduce infection rates, and build an effective foundation for future process improvement programs.